Laryngeal function and voice disorders basic science to clinical practice - Watts, Christopher R.; Awan, Shaheen N. (Thieme, 2019)
The definitive evidence-based resource on the diagnosis and treatment of voice disorders Laryngeal Function and Voice Disorders: Basic Science to Clinical Practice by renowned experts Christopher Watts and Shaheen Awan focuses on the latest developments in the assessment and management of voice disorders. New ASHA practice recommendations are included in accessible, digestible, and didactic content. This unique multimedia resource merges historical facts and experiential understanding with recent advances in scientific knowledge and evidence-based practice patterns. The book includes discussio